PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dina Arfianti Siregar; Entherthiman Galvani Tampubolon (JURNAL MANEKSI, 2019)
This study aims to determine the effect of profitability and company size on disclosure of social responsibility (CSR). Variable profitability and company size as an independent variable and disclosure of social responsibility (CSR) as the dependent variable. The number of samples used in this study were 35 manufacturing companies listed on the Indonesia Stock Exchange in 2014 to 2018. This study uses secondary data. Data were collected using a purposive sampling method based on certain conditions. Data were analyzed using linear regression models. The results of this study indicate that profitability does not affect to disclosure of social responsibility (CSR), while the firm size affects the disclosure of social responsibility (CSR).